ORIENTASI SEKSUAL DALAM FILM BROKEBACK MOUNTAIN KARYA SUTRADARA ANG LEE - Ponga, Julia Irene; Sigarlaki, Stephani J.; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â  Â  This research is entitled â€œOrientasi seksual dalam film Brokeback Mountain karya sutradara Ang Leeâ€. It is written to fulfill the requirements to complete undergraduate education majoring in English literature, Faculty of Humanities, Sam Ratulangi University. This study focuses on the sexual orientation depicted by the actors in the movie Brokeback Mountain. This research uses descriptive qualitative method by Bogdan and Biklen (1982) and used two theories to identify, classify, describes and analyze types of sexual orientation in Ang Lee's film Brokeback Mountain, the theory is the theory of J. Michael Bailey in his journal â€œ Sexual Orientation, Controversy, and Scienceâ€ (2016) and theory from Mario Klarer in his book â€œAn Introduction to Literary Studiesâ€ (2005). Based on the analysis of sexual orientation in the film Brokeback Mountain, it was found that the two main actors Ennis and Jack have an interest in each other, but on the other hand they have wives so it can be concluded that the two main characters in this film have a sexual orientation, namely bisexual.Keywords : Sexual Orientation, Literature and psychology, Film, Brokeback Mountain